Réponses

Meilleure réponse !
2014-06-09T11:04:39+02:00
Bonjour

(7x-1)(2x +6) = 0
soit 7x -1 = 0 ⇒ 7x = 1 et x = 1/7
soit 2x +6 = 0 ⇒ 2x = -6 et x = -3

(4x+5)² - (4x +5)(3x -1) = 0
(4x+5)(4x+5 - 3x +1) = 0
(4x +5)(x + 6) = 0

soit 4x +5 = 0 ⇒ 4x = -5 et x = -5/4
soit x +6 = 0 et x = -6

3(2x -6) = -5(3x +2)-4x
6x -18 = -15x - 10 -41x
6x +15x -41x = -10 +18
-20x = 8
x = - 8/20
x = - 2/5

3x² -27 = 12
3x²  = 12 +27
3x² = 39
x² = 13
x =√13

(5x -4)² = 16x²
(5x -4 -4x) ( 5x -4 +4x) = 0
(x -4)(9x -4) = 0
soit x-4 = 0 et x = 4
soit 9x -4 = 0 ⇒ 9x = 4 et x = 4/9

64x² -48x + 9 = 0
(8x +3)² = 0
(8x +3)(8x +3) = 0
8x +3 = 0 ⇒ 8x = -3 et x = -3/8


Merci beaucoup ! :)
Est-ce que tu peux m'expliquer d'où vient le 41x de la troisième équation stp.